Infant aphakia treatment study: Evaluation of cataract morphology in eyes with monocular cataracts - Wilson, M. Edward (2011)
PURPOSE: To describe a video-documented assessment of cataract type in eyes with monocular infantile cataract enrolled in the infant aphakia treatment study (IATS). METHODS: IATS is a randomized clinical trial comparing intraocular lens versus contact lens correction in 114 infants, aged 28 days to <7 months. A total of 83 videos were available for morphological analysis of cataract. Three examiners reviewed all surgical recordings and agreed on the cataract characteristics using a score sheet to record the lens layer or configuration of the opacity. RESULTS: Nuclear cataract was present in 45 of 83 eyes (54%). Posterior capsule plaque was seen in 73 eyes (88%). All eyes with fetal nuclear cataract had associated posterior capsule plaque. Cortical cataract without nuclear involvement was seen in 21 eyes (25%). Posterior bowing of the posterior capsule was noted in 4 eyes (5%). Evidence of persistent fetal vasculature (PFV) was present in 18 eyes (22%). PFV was the only finding in 5 eyes but was also seen in combination with nuclear (7 eyes) and cortical cataracts (6 eyes). The entire lens was white in 3 eyes (4%), while the lens was partially resorbed in 7 (8%) eyes. Anterior capsule fibrosis was noted in 5 eyes with advanced cataract (1 with total cataract, 4 with partially resorbed lens). CONCLUSIONS: Nuclear opacities were common, but many different cataract types presented in infancy. PFV occurred in isolation or in association with cataract. Posterior capsule plaque was frequently noted, especially when a nuclear cataract was present.